2022
DOI: 10.3390/bios12100825
|View full text |Cite
|
Sign up to set email alerts
|

An Origami Paper-Based Biosensor for Allergen Detection by Chemiluminescence Immunoassay on Magnetic Microbeads

Abstract: Food allergies are adverse health effects that arise from specific immune responses, occurring upon exposure to given foods, even if present in traces. Egg allergy is one of the most common food allergies, mainly caused by egg white proteins, with ovalbumin being the most abundant. As allergens can also be present in foodstuff due to unintended contamination, there is a need for analytical tools that are able to rapidly detect allergens in food products at the point-of-use. Herein, we report an origami paper-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The optimal GOx detection time was calculated by the saturation point (time constant, τ) in the kinetic curves (Figure S10a). The saturation time point for each concentration (1, 5, 20, and 40 mg/mL) was 3.00, 3.84, 7.60, and 6.33 min, respectively. Based on this result, the Glu@CPS-based GOx analysis time was set to an average time constant of 5 min (Figure S10b).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal GOx detection time was calculated by the saturation point (time constant, τ) in the kinetic curves (Figure S10a). The saturation time point for each concentration (1, 5, 20, and 40 mg/mL) was 3.00, 3.84, 7.60, and 6.33 min, respectively. Based on this result, the Glu@CPS-based GOx analysis time was set to an average time constant of 5 min (Figure S10b).…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the most widely used approaches is the use of the origami method by folding the paper into 3D stacks and holding it with pre-fabricated clamps. 48 Following fabrication, 3D μPADs are functionalized to enable the flow of samples in a regulated manner toward the detection zone for the analysis of results using detection meters. 20,49 Lee et al showed the effectiveness of 3D μPAD impregnated with HRP conjugated anti-Trx-1 antibody for the detection of breast cancer by targeting thioredoxin-1 with the detection limit of 0-200 ng ml −1 in the blood serum samples within 14 min.…”
Section: Microfluidic Paper-based Analytical Device (μPad)mentioning
confidence: 99%
“…135 In year 2022, Lazzarini et al created a 3D paper sensor using origami and wax printed ink for the detection of allergens in food sample. 136 It describes a sensor made of origami paper that uses magnetic microbeads to functionalize the paper substrate and conducts a competitive chemiluminescence immunoassay for ovalbumin in food samples. The schematic representation of the sensor as shown below in Fig.…”
Section: Design and Development Of 3d Paper-based Sensorsmentioning
confidence: 99%